Information needs of the inmates in Metro Manila District Jail at Camp Bagong Diwa - Bansig, Ann Grace B.; Lapuz, Elvira B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
The study determines the information needs of the inmates of Metro Manila District Jail. Specifically, the aims of the study are: to know the information needs of the inmates and their sources of information; to identify the materials they want in a library; to determine the role of the library in their rehabilitation and to develop a proposal for a jail library.
A questionnaire was designed to gather the necessary information. It consist of three parts, Part I: Personal Data; Part II: Information needs and resources; and Part III: Towards the development of a jail library.
The principal findings of the study are: 1. The respondents are relatively young. Forty five percent (45 percent) belongs to age bracket of 16-25; 2. Most of the respondents are in high school (70 percent) and elementary (11 percent) levels. Only (2 percent) are able to have a college degree; and 3. Most of the respondents have spent more than a year and in MMDJ (69 percent), others have spent less than a year and only (8 percent) spent more than a year.
When it comes to information needs, almost all of the respondents like to read and, if possible, want a place where they can read privately. Respondents believe that this will greatly fulfill their educational needs. Materials for the library are books on law and education; next are history and religion; followed by dictionaries and novels; lastly magazines, newspapers and poems.
Reading is both an educational and recreational activity. Through reading, time passes easily with enjoyment and learning. Therefore, development of a jail library is highly appropriate and very needed.
A proposed guideline for the establishment of the Metro Manila District Jail is hereby recommended.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Camp Bagong Diwa; Prisoners -- Philippines -- Manila Metropolitan Area -- Attitudes; Jail libraries -- Philippines -- Manila Metropolitan Area